EFFORT OF BHABINKAMTIBMAS IN PREVENTING THE DEVELOPMENT OF TERRORISME THROUGH SAMBANG IN THE JURISDICTION OF THE TEMANGGUNG POLICE - NAUFAL AQIL RIZQULLOH (Advances in Police Science Research Journal, 2022)
This research is motivated by the rise of arrests of terrorists who are hiding, settling, and living in Temanggung. One thing that poses a threat to the rise of arrests of terrorists is the spread of terrorism in the community. One of the preventive measures used by the national police is a preemptive effort with the technical function of Binmas as one of the implementers. Through members of the Bhabinkamtibmas, it is hoped that one way of acting by conducting Sambang can prevent the development of the spread of terrorism in Temanggung. the purpose of this study was to find out Sambang implementation carried out by Bhabinkamtibmas in preventing the development of terrorism in Temanggung, as well as to find out the efforts made by Bhabinkamtibmas in preventing the development of terrorism in Temanggung. This research method is carried out using a qualitative approach and the type of research is grounded theory. Data collection techniques by conducting interviews, observations, and document studies. The use of POAC management theory by George R Terry to carry out an analysis of the implementation of Sambang carried out by Bhabinkamtibmas, as well as crime prevention theory according to Awaloedin to conduct an analysis of the efforts made by Bhabinkamtibmas in preventing the development of terrorism through active Sambang. Based on the results of the study, it was found that the implementation of Sambang has not been carried out based on Perkap no 7 of 2021 concerning Bhabinkamtibmas and the Bhabinkamtibmas smart book edition V of 2018. The efforts made by Bhabinkamtibmas have also not been carried out properly which is influenced by several factors causing it. From the result of this study, the authors suggested problem solving to the Bhabinkamtibmas and Sat Binmas Temanggung to pay more attention to the implementation of sambang and the efforts made by Bhabinkamtibmas in order to achieve the goal of preventing development of terrorism in Temanggung and the creation of Harkamtibmas.